Immortalized Hepatocytes Using Human Artificial Chromosome - Masahiro Ito M.D., Ph.D.; Ryoutaro Ito; Daisuke Yoshihara; Masashi Ikeno; Megumi Kamiya; Nobutaka Suzuki; Akihiko Horiguchi; Hideo Nagata; Toshiyuki Yamamoto; Naoya Kobayashi; Ira J. Fox; Tsuneko Okazaki; et al. (Cell Transplantation, 2008)
The shortage of organ donors has impeded the development of human hepatocyte transplantation. Immortalized hepatocytes could provide an unlimited supply of transplantable cells. To determine whether immortalized hepatocytes could provide global metabolic support in end-stage liver disease, rat hepatocyte clones were developed by transduction with the gene encoding the Simian virus 40 T antigen (SVT) using the human artificial minichromosome (HAC). The SVLT sequence was excised by FRT recombination. Following HAC infusion, the transduced hepatocytes express SVT, blasticidine resistance (BS), and the PGK promoter TK gene. Forty-six cell clones were obtained and at least partially characterized, as previously described, for albumin, α-1-antitrypsin, glucose-6-phosphatase (G6Pase), dipeptidylpeptidase 4 (Dpp4), γ-glutamyltransferase 1 (Ggt), SVT, and β-actin expression using RT-PCR. Clones were also assessed for albumin secretion into the culture medium using ELISA. All of the cell line secreted approximately 10 mg/dl of albumin, which is equivalent to the amount secreted by primary hepatocytes. In further experiments, this cell line will be used for transplantable cells or artificial organ using HAC. These results represent an important step toward the development of immortalized hepatocytes.